Geología de los cuadrángulos de Bolívar, Curaray, Santa Clotilde, Quebrada Aguablanca, Quebrada Sabaloyacu, San Lorenzo, Intuto, Río Pintoyacu, Río Mazán, Río Corrientes, Libertad, Río Nanay, Santa Rosa, Yacumama, Río Itaya, Yanayacu, Chapajilla y Nauta – [Boletín A 131] - Martínez Valladares, William (1999)
372 p., 18 mapas